ARTIFICIAL INTELLIGENCE IN SPORT PERFORMANCE ANALYSIS - Araujo, Duarte; Couceiro, Micael; Seifert, Ludovic; Sarmento, Hugo; Davids, Keith (Routledge, 2021)
To understand the dynamic patterns of behaviours and interactions between athletes that characterise successful performance in different sports is an important challenge for all sport practitioners. This book guides the reader in understanding how an ecological dynamics framework for use of artificial intelligence (AI) can be implemented to interpret sport performance and the design of practice contexts. By examining how AI methodologies are utilised in team games, such as football, as well as individual sports, such as golf and climbing, this book provides a better understanding of the kinematic and physiological indicators that might better capture athletic performance by looking at the current state-of-the-art AI approaches. Artificial Intelligence in Sport Performance Analysis provides an all-encompassing perspective in an innovative approach that signals practical applications for both academics and practitioners in the fields of coaching, sports analysis, sport science as well as related subjects such as engineering, computer and data science, and statistics.